PENERAPAN PROGRAM PHBS TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT PADA ANAK USIA SEKOLAH DASAR KELURAHAN KANIGARAN RT 06 RW 02 KOTA PROBOLINGGO - Eka Diah Kartiningrum, M.Kes; Karina Fahmi Amilia (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
PHBS is behavior observed by educated, teachers, and other awareness-school residents, thereby independently being able to prevent disease, improve their health, and contribute actively to the development of health. The purpose of this study aimed to now the application of the PHBS program for clean living behavior and heath iesgrade school children RT 02 RW 06 city of probolinggo. It’s the result of this research exhibiting PHBS elementary school age children indicate that p thereis a good category of 27 (90%) whereas in a category quite as much as 3 (10%). To the data analysis used there is a good category of 27 (90%) whereas in a category quite as much as 3 (10%). The data analyzed by wilcoxon signed tests showed significant differences before and after werw given the PHBS programme to children. Applying his PHBS consistently with teacher supervision could be done, and parents would then enhance the quality of health and lower the school-age children’s vulnerability to potential health problems.